Taravana syndrome and posterior reversible encephalopathy syndrome: a microbubble hypothesis for neurological accidents in breath-hold divers - Druelle, Arnaud; Castagna, Olivier; Roffi, Romain; Louge, Pierre; Faivre, Anthony; Blatteau, Jean-Eric (Frontiers in Physiology, 2024)
Breath-hold diving is a challenging activity that can lead to serious and dangerous complications, such as the "Taravana" syndrome. This syndrome is characterized by the onset of neurological symptoms after deep or repeated dives. The main clinical manifestations are cerebral, including stroke and cognitive impairment. The pathophysiology of Taravana syndrome is still widely debated, but the most accepted theory is that it is a specific form of decompression sickness. We have reviewed the main theories explaining the onset of Taravana syndrome and, through the description of a particularly illustrative case of a freediver using an underwater scooter, we have formulated a hypothesis according to which micro-bubbles formed directly in cerebral structures would be at the origin of this syndrome. MRI showed diffuse encephalopathy with vasogenic edema. Analysis of the radiological sequences did not suggest an ischemic or embolic mechanism. This finding is likely to be associated with the diagnosis of posterior reversible encephalopathy syndrome. The rapid ascent speeds associated with underwater scooter use could potentially result in the formation of nitrogen micro-bubbles in the capillaries of brain tissue. The emergence of scooters in freediving can be a hazard because of their ability to facilitate very rapid ascents. It is therefore essential to take preventive measures to ensure the safety of users of these devices.